Willingness to participate in, support or carry out scientific studies for benefit assessment of available medical interventions: A stakeholder survey - Stadelmaier, Julia; Meerpohl, Joerg J.; Toews, Ingrid (PLOS ONE, 2022)
Background Post-entry studies are a key element in managed entry agreements and aim at generating evidence about the additional benefit of new medical interventions before reimbursement decisions are made. This study evaluates the willingness of different stakeholder groups to engage post-entry in studies for benefit assessment and to assess differences in their willingness by study type, i.e. randomised controlled trial or observational study. Methods We conducted a cross-sectional, web-based survey with a self-administrated questionnaire in German language. We disseminated invitations to patients, patient representatives, healthcare providers, trialists & scientists and representatives of the medical private sector, using a snowball system, public contact details of German associations and organisations, and social media. We analysed quantitative data descriptively and qualitative data inductively. Results Data of 154 respondents were available for analysis. The majority (>85%) was willing to engage in the studies in general, and regarding different study types. Scientists reported a higher willingness to conduct and support RCTs (p = 0.01) as compared to observational studies. Representatives of the private sector were mainly willing to support, but not to carry out post-entry studies. Stakeholders frequently mentioned that potential personal benefit and altruistic motives were relevant for their decision to engage in studies. Practical inconveniences, poor integration into daily life, high demand for time and personnel, and lack of resources were commonly mentioned barriers. Discussion and conclusion Stakeholders clearly reported to be willing to engage in post-entry studies for benefit assessment. Self-reported willingness to participate in and support for studies seems higher than practical recruitment rates. The survey might be subject to survey error and self-enhancement of participants. Inquiring about the willingness of hypothetical studies might have caused participants to report higher willingness. Motives for and against participation may be possible starting points for approaches to overcome recruitment difficulties and facilitate successful study conduct.